A teacher training workshop to promote the use of the VISIR Remote Laboratory for electrical circuits teaching - Arguedas, Carlos (2018)
The learning of Physics involves building up and using lab experiments. In turn, teachers must be trained in experimenting and using several resources that enable them to design valuable teaching strategies and learning activities. Thanks to Information and Communication Technologies (ICT), virtual and remote labs can provide a framework where physical experiments can be developed. Altough remote labs have been in use for over a decade now in several countries and levels of education, its use at secondary schools in Latin America has not been reported yet. The Virtual Instruments System in Reality (VISIR) is one of these remote labs, suitable to practice in the area of electrical circuits. This paper aims at describing how this remote lab was used in a training workshop for secondary school level teachers of Physics in Costa Rica.